2009
DOI: 10.1073/pnas.0901890106
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin is an anabolic bone hormone

Abstract: We report that oxytocin (OT), a primitive neurohypophyseal hormone, hitherto thought solely to modulate lactation and social bonding, is a direct regulator of bone mass. Deletion of OT or the OT receptor (Oxtr) in male or female mice causes osteoporosis resulting from reduced bone formation. Consistent with low bone formation, OT stimulates the differentiation of osteoblasts to a mineralizing phenotype by causing the up-regulation of BMP-2, which in turn controls Schnurri-2 and 3, Osterix, and ATF-4 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
294
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 234 publications
(307 citation statements)
references
References 35 publications
11
294
1
1
Order By: Relevance
“…osteoporosis | osteoblast | skeleton O ver the past decade, we have described direct actions of anterior and posterior pituitary hormones on the skeleton (1)(2)(3)(4)(5)(6)(7)(8). We have shown that these actions are exerted via G protein-coupled receptors resident on both osteoblasts and osteoclasts.…”
mentioning
confidence: 99%
“…osteoporosis | osteoblast | skeleton O ver the past decade, we have described direct actions of anterior and posterior pituitary hormones on the skeleton (1)(2)(3)(4)(5)(6)(7)(8). We have shown that these actions are exerted via G protein-coupled receptors resident on both osteoblasts and osteoclasts.…”
mentioning
confidence: 99%
“…However, this effect is in contrast to uterine myocytes, wherein pErk is reduced in mice lacking either Arrb1 or Arrb2 (26). The intactness of the pErk response in osteoblasts could be explained by the known activation of MAPKs by G αi and G αq (28); this actin could account for the positive effect of Oxt on osteoblast viability that we have shown earlier (4).…”
Section: Discussionmentioning
confidence: 53%
“…We have shown previously that osteoblasts express abundant plasma membrane Oxtrs that drive cell differentiation to a mature, mineralizing phenotype in response to pituitary-and bone marrow-derived Oxt (4,6). However, the mechanism of this effect has remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations